Grain boundary sliding associated with low strain rate at 1000 °C in recrystallized ODS ferritic steel. (December 2016) - Kamikawa, R.; Ukai, S.; Oono, N.; Kaito, T.; Torimaru, T.; Kimura, A.; Hayashi, S.; Masuda, H.; Sato, E.
Abstract: The high-temperature deformation process of the recrystallized 16CrODS ferritic steel was investigated at 1000 °C for the stress loading perpendicular to the elongated grain structure. The strain rate was varied in the range from 1.0 × 10 −2 to 1.0 × 10 − 5  s −1 . At the strain rate over 1.0 × 10 − 4  s −1, deformation is dominated by the conventional dislocation creep. Decreasing strain rate from 1.0 × 10 − 4  s −1, grain boundary sliding becomes prominent. Accommodation process for the localized stress induced by grain boundary sliding could be dislocation creep at 1.0 × 10 − 4  s −1, and by diffusional creep at 1.0 × 10 − 5  s −1 or less. These were verified through the observation of void formation and localized strain accumulation by KAM map.